Pemanfaatan Lahan Perkotaan untuk Memaksimalkan Lahan Perkotaan yang Terbatas Bersama Ibu-Ibu PKK - Dimas Aditiya; Lili Dasa Putri; Solfema Solfema (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
This literature study examines hydroponic solutions (urban agriculture), particularly through hydroponic methods, as a response to the issue of significant urban agricultural land shrinkage and land conversion. Data shows a drastic reduction in rice fields in Sukawati District, Bali, from 497.24 Ha in 1985 to only 211.42 Ha in 2016, accompanied by a change in the profession of residents from farmers to entrepreneurs. This land conversion not only reduces agricultural areas but also has the potential to eliminate farmers' livelihoods. The method used is a literature review (narrative review) to collect and analyze studies related to the use of hydroponics in maximizing limited land in urban areas. The results of the discussion focus on hydroponic training provided to housewives from the Family Welfare Movement (PKK) and the City Youth Organization (Karang Taruna). This training aims to empower and utilize the free time of housewives, covering materials from the basic concepts of hydroponics, seed preparation, planting, maintenance, to harvesting. Hydroponic practices have been responded to positively by residents, and the PKK/Karang Taruna group is prepared to become mentors for other members. The benefits of hydroponics were emphasized as a highly efficient cultivation method, capable of saving up to 70-90% of water, enabling year-round food production, and providing faster and higher plant growth and yields. The outcome of this activity was the establishment of a communal hydroponic garden and each member's plan to grow hydroponically independently, demonstrating the success of hydroponics as a real solution to improving food security and sustainability in dense urban environments.